VD_FINDINFO Décision / 2014 / 1120 vom 18. Dezember 2014 - VD Tribunal cantonal (2014)
RETRAITVOIE DE DROIT, INDEMNITÉEN GÉNÉRAL, AVOCAT D'OFFICE, DÉCISION SUR FRAIS | 135 CPP (CH), 396 CPP (CH), 398 al. 2 CPP (CH)